Hubungan kejadian eating disorder dengan status gizi remaja putri di Denpasar, Bali - Made Violin Weda Yani; Made Sindy Astri Pratiwi; Made Priska Arya Agustini; Putu Cintya Denny Yuliyatni; I Gede Putu Supadmanaba (Intisari Sains Medis, 2022)
Background: Nutrition problems in adolescents both malnutrition and overnutrition in Indonesia are quite high. Nutrition problems are multifactorial, but several previous studies have shown that eating behavior will interfere with eating disorders related to nutritional quality. This study aims to analyze the relationship between eating attitude and eating disorders on nutritional status in adolescent girls. Methods: This research design was cross sectional observation conducted at SMAN 1 Denpasar, Bali. The samples were 119 adolescent girls that were selected by simple random sampling. Assessment of eating behavior used the adolescent food habit checklist, and eating disorders were assessed by EAT-26 questionnaire. Results: The subjects were 119 adolescent girls. Most of them were 15 and 16 years old. There were 53.8% of subjects having unhealthy food behavior and 86.6% did not experience eating disorders. There were 75.6% of students having normal nutritional status, followed by thin, overweight, and obese respectively 3.4%, 15.1%, and 5.9%. There was a significant relationship between eating attitude with nutritional status of adolescent girls (p value = 0.04; PR (95% CI) = 2.15 (1.09-4.21)). There is also a significant relationship between eating disorder with nutritional status of adolescent girls (p value=0.01; PR (95% CI) = 2.45 (1.32-4.56)) Conclusion: This study found that eating behavior was not related to nutritional status. The condition of eating disorders has a significant relationship with adolescent nutritional disorders. Individuals with eating disorders have a greater risk of experiencing nutritional disorders than individuals without eating disorders.   Latar Belakang: Masalah gizi pada remaja baik undernutrition ataupun overnutrition di Indonesia cukuplah tinggi. Masalah gizi pada remaja bersifat multifaktorial, namun beberapa penelitian sebelumnya menunjukkan bahwa faktor perilaku makan yang tidak baik akan memicu eating disorder yang berhubungan dengan kualitas gizi remaja putri. Sejauh ini belum terdapat studi terkait hubungan eating disorder dengan status gizi remaja putri di Bali. penelitian ini bertujuan untuk menganalisis hubungan antara perilaku makan dan eating disorder terhadap status gizi pada remaja putri. Metode: Desain penelitian yaitu observasi cross sectional yang dilakukan di SMAN 1 Denpasar, Bali. Sampel berjumlah 119 orang remaja putri berusia 14-18 tahun yang dipilih dengan simple random sampling. Penilaian perilaku makan menggunakan the adolescent food habbit checklist, dan gangguan makan dinilai menggunakan kuesioner EAT-26. Hasil: Dari 119 subjek penelitian, dominasis siswi putri berusia 16 tahun. Sebanyak 53.8% remaja putri memiliki perilaku makanan yang tidak sehat dan 86.6% tidak mengalami eating disorder. Mayoritas siswi memiliki status gizi yang normal yaitu 75.6%, diikuti dengan status gizi kurus, gemuk, dan obesitas berturut-turut yaitu sebesar 3.4%, 15.1% dan 5.9%. Terdapat hubungan yang signifikan antara perilaku makan buruk dengan gangguan gizi (p value=0.049; PR(95%CI) = 0.52 (0.27-1.01)) dan terdapat pula hubungan yang signifikan antara eating disorder dengan gangguan gizi remaja putri (p value=0.01; PR (95% CI) = 2.45 (1.32-4.56)) Simpulan: Penelitian ini mendapatkan bahwa perilaku makan dan kondisi eating disorder memiliki hubungan signifikan dengan gangguan gizi remaja putri.  Individu dengan eating disorder memiliki risiko lebih besar mengalami gangguan gizi dibandingkan individu tanpa eating disorder.